ENHANCING EMPLOYEES’ WORK PASSION THROUGH WORKPLACE RELATIONSHIP MANAGEMENT STRATEGIES IN THE NIGERIAN BANKING INDUSTRY (American Journal of Research in Humanities and Social Sciences, 2024)
The research investigated the relationship between workplace relationship management strategies (WRMS) and employees’ work passion (EWP) within the Nigerian banking industry. A sample of 160 managers and supervisors from 20 randomly selected banks in the Niger Delta Region of Nigeria was utilized. A quasi-experimental research design was used, and data were collected through a cross-sectional survey using a questionnaire. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS) Version 25, utilizing structural equation modeling (SEM) via the AMOS package. The results reveal a positive and significant correlation between workplace relationship management strategies (WRMS) and employees’ work passion (EWP) in the Nigerian banking industry. Specifically, the findings illustrate a robust positive and significant correlation between trust, a dimension of workplace relationship management strategies, and the metrics of employees' work passion (namely, harmonious passion and obsessive passion). Similarly, the research identifies a strong positive and significant correlation between shared values and goals, another dimension of workplace relationship management, and the metrics of employees' work passion (harmonious passion and obsessive passion). Consequently, the study concludes that trust and shared values and goals significantly bolster employees’ harmonious passion and obsessive passion, respectively, within Nigerian deposit money banks. The theoretical and managerial implications of these findings were also discussed.